If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4x+89=-7x-164
We simplify the equation to the form, which is simple to understand
4x+89=-7x-164
We move all terms containing x to the left and all other terms to the right.
+4x+7x=-164-89
We simplify left and right side of the equation.
+11x=-253
We divide both sides of the equation by 11 to get x.
x=-23
| -23-5x=10x+16 | | -132=3x+3(-7x-2) | | 11(m-2)=0 | | -6y+6=7y+9 | | 2(x+4)=-5+1 | | -70+2x=-4x+32 | | 100-(x+2)=x/2 | | 75=-3(-6n-5) | | 256x^2-225= | | -3(x+2)+4(3x-8)=2(4x+7)+2(3x-6) | | -55-12x=-5x+36 | | (4x+9)(x-7)= | | 2(x+4)=-5x | | 2x+4=-5x+1 | | 49n^2-81=0 | | 100=(x+2)+(x/2) | | -28=92+10x | | 100=x+2+x/2 | | 2(2w+12)=68 | | 4x-2(-1x-11)=64 | | 25a^2-80a+64=0 | | Z^2+8=4 | | a+(37+a)+(2a-40)=433 | | s-32=-29 | | 2x+8=352 | | (x)(x+1)(x+2)=36 | | 8x-(5x+4)=7+(2x-3) | | -5x+4(-3+3)=-192 | | x^2*y-3*x*y=0 | | 5(2a+4)=6a-4 | | 1.2m=.6 | | (x^2-5x-3)(x^2-5x-5)=3 |